Energetic Effects of Pre-hatch Albumen Removal on Embryonic Development and Early Ontogeny in Gallus gallus - Peña-Villalobos, Isaac; Piriz, Gabriela; Palma, Verónica; Sabat, Pablo (Frontiers in Physiology, 2017)
Studies on the yolk and albumen content in bird eggs, and the effects of variations in their relative loads in the phenotype of the birds, have revealed multiple consequences at different levels of biological organization, from biochemical traits to behavior. However, little is known about the effect of albumen variation on energetics performance during development and early ontogeny, despite the fact that variation in energy expenditure may have consequences in terms of fitness for both feral and domestic species. In this work, we evaluated experimentally whether variations in the content of albumen of Gallus gallus eggs could generate differences in metabolic rates during embryonic development. Additionally, we assessed changes in the activity of mitochondrial enzymes (cytochrome c oxidase and citrate synthase) in skeletal muscles and liver. Finally, we evaluated the success of hatching of these embryos and their metabolic rates (MR) post hatching. The results revealed a significant reduction in MR in the last fifth of embryonic life, and reduced catabolic activities in the skeletal muscle of chicks hatched from albumen-removed eggs. However, the same group demonstrated an increase in catabolic activity in the liver, suggesting the existence of changes in energy allocation between tissues. Besides, we found a decrease in hatching success in the albumen-removed group, suggesting a negative effect of the lower albumen content on eggs, possibly due to lower catabolic activities in skeletal muscle. We also found a compensatory phenomenon in the first week after hatching, i.e., birds from albumen-removed eggs did not show a decrease in MR either at thermoneutral temperatures or at 10º C, compared to the control group. Collectively, our data suggest that a reduction in albumen may generate a trade-off between tissue metabolic activities, and may explain the differences in metabolic rates and hatching success, supporting the immediate adaptive response (IAR) hypothesis.